Analysis of Embryo Development and Early Performance of Larvae of Barbonymus Schwanenfeldii: A Systematic Review - Mafruchati, Maslichah; Makuwira, Jonathan (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2022)
Tengadak fish is a freshwater fish that can be found in rivers, lakes and canals and ditches. One of the important phases in fish development is the embryo. Embryo development (embryogenesis) is more in the process of formation and development of the embryo, not only the increase in the number and mass of embryonic blastomer cells but also the activity of blastomeric cells.The purpose of this study was to analyze the stages of embryonic development and early larval performance in Tengadak fish (Barbonymus schwanenfeldii). This study used systematic literature review using data from PubMed, NCBI, Google Scholar databases using keywords, namely, “embryo, performance, Tengadak fish (Barbonymus schwanenfeldii)”. Approximately, 350 articles were obtained for the keywords “embryo, performance, Tengadak fish (Barbonymus schwanenfeldii)”. All articles were selected based on inclusion criteria and exclusion and obtained as many as 27 articles that meet the inclusion criteria From the results of research conducted, it can be concluded that this research has sequentially described the embryonic development and early performance of the larvae of the barbonymus schwanenfeldii. Need research on the other animal for future research.